Existence and uniqueness analysis of a non-isothermal cross-diffusion system of Maxwell–Stefan type. (January 2018) - Hutridurga, Harsha; Salvarani, Francesco
Abstract: In this article we prove local-in-time existence and uniqueness of solution to a non-isothermal cross-diffusion system with Maxwell–Stefan structure.